DETERMINANTS OF ENVIRONMENTAL DISCLOSURE - Effriyanti; Belinda (ZILLZELL MEDIA PRIMA, 2023)
This research aims to analyze and obtain empirical evidence of the determinants of environmental disclosure of basic materials sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2022. This research is quantitative research with associative methods. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. Samples were collected using the purposive sampling method. The amount of data collected was 105 data. The data was processed using the Eviews 9 Statistical Program to test the hypothesis using panel data regression analysis with the REM (Random Effect Model) model which was chosen as the most appropriate model analysis. The results show that institutional ownership, audit committee size, and environmental performance simultaneously influence environmental disclosure. Partial institutional ownership has no effect on environmental disclosure. The size of audit committee partially influences environmental disclosure. Environmental performance partially influences environmental disclosure.